High-performance thin-layer chromatography (HPTLC) - Srivastava, ManMohan (Springer, 2011)
The book is organized in four chapters comprising of 18 contributions from experts of international repute. The book highlights HPTLC system as a versatile modern analytical technique with reference to its excellent automation, optimization, multidimensional applications. It deals with fundamentals, principle, theory of HPTLC based separation, experimental details, handling understanding and implementation. It describes various applications of HPTLC separation with special reference to phytochemical analysis, fingerprint analysis, authentication, biomedical analysis, drug quantification, analytical analysis, quantitative analysis and validation. HPTLC and its future in combinatorial approach adds new dimension for its potential for hyphenation, HPTLC-MS coupling, laser desorption-HPTLC chromatography coupled with chemical ionization mass spectrometry etc.